The internationalization of higher education : concepts, cases, and challenges - Apaydin, Marina; Branch, John, 1967-; Dent, Michael M.; Regalado Pezúa, Otto (Contemporary issues in higher education (Charlotte, N.C.), 2023)
"The internationalization of higher education is as old as the university itself. Indeed, the University of Karueein, which is the world's oldest higher education institution, has welcomed Muslim students from across the Islamic world since its founding in 859. But the internationalization of higher education continues to be a subject of immense interest, to scholars and practitioners alike, as both its substance and scope transform and transfigure in concert with political, social, and economical changes. Consider the growth of the so-called 'virtual exchange' which has been enabled by the internet, and which has accelerated as a result of the COVID-19 pandemic. This anthology presents contemporary concepts, cases, and challenges of the internationalization of higher education. Its 14 chapters span the aim to contribute to our understanding of the nature of the internationalization of higher education, of the mechanisms of the internationalization of higher education, and of the applications of the internationalization of higher education. For scholars, the anthology will enliven the discourse on the internationalization of higher education; for both higher education policy-makers, administrators, and leaders, it will serve as both an inspiration and a practical guidebook"--